Effects of non-oarside-arm pull on the forces at the handle and foot-stretcher in sweep-rowing - Mattes, K.; Manzer, S.; Schaffert, N.; Reischmann, M.; Böhmert, W. (Journal of Sport and Human Performance, 2016)
In sweep-rowing the rotational movement of the oar-handle around the swivel is executed by the arm and shoulder and results in an asymmetry between the body sides. The non-oarside-hand (-arm, -shoulder and -leg) pulls with a longer lever and more tangentially at the handle than the oarside-arm. Aim of the study was to examine the non-oarside-arm-force and its effect on the longitudinal, normal force at the oar-handle, and on the stretcher-force of the non-oarside- and oarside-leg.